The Influence of Early Grade Reading On Pupils Academic Performance in Selected Primary Schools in Rukiga District - Muhumuza, Boaz (Kabale University, 2022)
A Research Report Submitted to the Faculty of Education in Partial Fulfilment of the Requirement for the Award of Bachelors Degree of Education Primary of Kabale University.